KOMUNIKASI PERSUASIF GURU DALAM MEMBENTUK KARAKTER RELIGIUS SISWA DI SDIT ZAID BIN TSABIT KECAMATAN KERUMUTAN KABUPATEN PELALAWAN - Patmawati, Pramadita; Susanti, Hevi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
SDIT Zaid bin Thabit is an Islamic-based school which has a vision and mission of intro-ducing and implementing religious habits to students. The focus of this research is the process car-ried out by the teachers at SDIT Zaid bin Thabit in forming religious character in students. such as it is difficult to follow memorization rules and children who enter school cannot yet read the Ko-ran. With the aim of analyzing how the process occurs in persuasive message communication car-ried out by teachers to students and to find out how teachers maintain the effectiveness of persua-sive communication carried out in forming students' religious character and to find out what ob-stacles are faced in the persuasive communication process which was carried out at SDIT Zaid bin Thabit. The method used in this research is qualitative with a descriptive approach. This research was conducted using data collection techniques of in-depth interviews, observation and documen-tation. The selection of informants was carried out using purposive sampling technique. Data col-lection techniques in this research took the form of in-depth interviews, observation and documen-tation. For data analysis techniques the author uses data reduction, data presentation and draw-ing conclusions. The results of the research show that SDIT Zaid bin Thabit teachers use the role model method, wisdom method and halaqoh talqin method, utilize infocus media, speakers and posters in conveying and instilling their teachings and hold a boarding program one night every week where students will be familiarized with the activities of students in carrying out various religious ser-vices, which aim to be implemented in their daily lives. And the obstacles faced are limited time, teaching between school and at home which is sometimes different, students who spend a lot of time playing online games and imitating the words in the game and copying a lot of what they see and hear on social media.